The Identity Crisis of Jeng Yah in the “Gadis Kretek” Movie: The Study of Erick H. Erikson's Developmental Psychology - Jannah, Anis Faikatul; Raras Hafiidha Sari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The study aims to analyze the identity crisis conflicts of Jeng Yah characters in the film